Analysis of the Performance of the Legal Subdivision of the Meranti Islands Regency KPU Secretariat in facing the 2020 Regent and Deputy Regent Election - Bherry Tinanto; Roni Ekha Putera (Department of State Administration - Musamus University, 2024)
The vacant position of Head of the Legal Subdivision of the Meranti Islands Regency KPU Secretariat has been going on since 2017. From 2017 to 2020 there were several major agendas for democratic parties including the 2018 simultaneous Regional Head Election, the 2019 General Election, the 2020 Simultaneous Regional Head Election and the General Election 2024. Usually this definitive position vacancy is not allowed to continue for a long time because it will affect the effectiveness of the organization in providing public services and is related to organizational performance. This research aims to explain how the Legal Subdivision of the Meranti Islands Regency KPU Secretariat performed during the absence of the Head of Definitive Law Subdivision in the 2020 Meranti Islands Regent and Deputy Regent Election. This research was conducted using qualitative methods. This research looks at organizational performance through five indicators, namely productivity, service orientation, responsiveness, responsibility and accountability. The results of this research explain that the performance of the Meranti Islands Regency KPU secretariat can be said to be good but has not yet run optimally because there are still obstacles in the way due to the absence of a definitive legal subdivision head.